San Jose YWCA annual meeting - Martin & Rita Rowe (photographic studio):::Creator::::::::::::
Photograph shows the left side of the head table where Mrs. Jemimah Gecaga, Kenya YWCA president, is sitting. She is not in the photograph. The three women pictured are (left to right): Mrs. John Goldsborough, standing, Mrs. Fred May, and Mrs. Sargent (Lucille) Wright. There are three unidentified men at the same table.